Metode Geographically Weighted Lasso dalam Pemodelan Tingkat Pengangguran Terbuka di Sulawesi Selatan - Isnaini, Wulan Maulia; Aswi, Aswi; Sudarmin, Sudarmin (ESTIMASI: Journal of Statistics and Its Application, 2025)
The Open Unemployment Rate (TPT) in South Sulawesi which reached 6.07% in 2020 has an impact on the economy and welfare levels. TPT data in South Sulawesi has spatial diversity. To overcome spatial diversity in data analysis, the Geographically Weighted Regression (GWR) method can be used. However, GWR is less than optimal if multicollinearity occurs, so the Geographically Weighted Lasso (GWL) method is more appropriate. Research related to GWL on TPT in South Sulawesi has not been conducted. This study aims to obtain a GWL model with a spatial weighting matrix using a fixed exponential kernel weighting function and identify factors that influence TPT. The data used are TPT, population growth rate, literacy rate, illiteracy rate, average length of schooling, job vacancies, and job seekers. The results of the study showed that the factors influencing TPT were population growth rate, illiteracy rate, average length of schooling, and job vacancies in several districts/cities with an R2 value of 89.4%.